Chewing gum vs. ibuprofen in the management of orthodontic pain, a multi-centre randomised controlled trial – the effect of anxiety. (2nd January 2017) - Ireland, Anthony J.; Ellis, Pamela; Jordan, Abbie; Bradley, Rebecca; Ewings, Paul; Atack, Nicola E.; Griffiths, Helen; House, Kate; Moore, Matthew B.; Deacon, Scott; Wenger, Nicholas; Worth, Victoria; et al.
ABSTRACT: Objectives: Pain is a common side effect of orthodontic treatment. An objective of this study, part of a large previously reported RCT on pain and analgesic use, was to determine the effect of anxiety on perceived pain and use of analgesia. Methods: 1000 patients aged 11–17 years, undergoing upper and lower fixed appliance treatment in nine hospital departments were recruited into this two-arm parallel design randomised controlled trial. One arm was given sugar-free chewing gum and the other arm ibuprofen for pain relief. Neither the clinicians nor patients were blinded to assignment. In addition to recording pain experience and analgesic use for 3 days following appliance placement and first archwire change, each patient recorded their level of anxiety immediately following the fitting of the appliance and the first archwire change. Results: 419 chewing gum group (84%) and 407 ibuprofen group (83%) questionnaires were returned following appliance placement, and 343 chewing gum group (70%) and 341 ibuprofen group (71%) questionnaires were returned following the first archwire change. The mean anxiety scores following fitting of the appliance and first archwire change were 2.7 (SD 2.1) and 1.6 (SD 1.8), respectively. There were weak but significant positive associations between anxiety scores and pain scores. Multi-level modelling produced a coefficient for anxiety of 0.23 (95% CI 0.17–0.28) for appliance placement, suggesting a small rise (0.23) on the 11-point pain scale for a one-point increase on the corresponding anxiety scale. Following archwire change, the corresponding coefficient was 0.32 (0.24–0.39). For ibuprofen use, again simple analyses suggested a relationship with anxiety. Multi-level logistic modelling produced an odds ratio for ibuprofen use of 1.11 (95% CI 1.07–1.15) at appliance placement and 1.21 (1.10–1.33) at the first archwire change. There was a 10–20% increase in the odds of using ibuprofen for each one-point increase on the anxiety scale. No such relationship was found between anxiety and chewing gum use. There were no adverse effects or harms reported during the trial. Approvals were granted by the Research Ethics Committee (08/H0106/139), R&D and MHRA (Eudract 2008-005522-36) and the trial was registered on the ISRCTN (79884739) and NIHR (6631) portfolios. Support was provided by the British Orthodontic Society Foundation. Conclusions: There was a weak positive correlation between anxiety reported and pain experienced following both the initial fitting of the fixed appliances and at the subsequent archwire change. Patients that were more anxious tended to take more ibuprofen for their pain relief.